Focused Research on the Challenges and Productivity of Researchers in Nigerian Academic Institutions Without Funding - Igiri, Bernard E.; Okoduwa, Stanley I. R.; Akabuogu, Ebere P.; Okoduwa, Ugochi J.; Enang, Idongesit A.; Idowu, Olanipekun O.; Abdullahi, Suleiman; Onukak, Imeh E.; Onuruka, Catherine C.; Christopher, Ogechukwu P.O.; Salawu, Akinbobola O.; Chris, Aimee O.; et al. (Frontiers in Research Metrics and Analytics, 2021)
Background: The challenge of research funding constraints has brought to bear enormous pressure on researchers. Research productivity is relevant to prestige and career progression of academic staff. However, this study aimed to explore significant challenges associated with researchers’ productivity and the impact of non-funding of research in Nigeria research and tertiary institutions. Methods: This study adopted a qualitative exploratory design involving academics at various research and tertiary institutions across the six geographical regions in Nigeria. A semi-structured questionnaire was distributed electronically to all participants who consented to take part in this study. Exactly 4,159 questionnaires were administered and 2,350 were completely filled and returned. Pearson correlation matrixes with logistic regression was used for data analysis and presented in frequencies and percentages. Results: On challenges faced by respondents, 42.98% reported lack of research funding, 17.11% consented to brain drain challenge while 8.85% indicated lack of motivation. Of the 23,927 number of publications reported, the research publication of those in sciences, engineering and medical sciences were average of 9.6, 11.5 and 9.5 respectively. The average number of publication per female (10.8) was more than the male (9.7). The lecturers had the highest average research publication (11.8) followed by researchers (10.2) and others (3.9). The male had the highest (11.9) average number of conferences than female (9.2). Participants in engineering had 13.8 average number of conferences per respondents followed by those in education (11.2), sciences (11.1) and 10.9 for those in agricultural sciences. The result revealed a negative significant correlation between research publication and academic qualification at p ˂ 0.01. Positive significant correlation was observed between research productivity and discipline at p ˂ 0.05. Finding shows that the combined influence of the independent variables to the research productivity was significant using linear regression analysis. Conclusions: The failure to prioritise research has resulted in underdevelopment in Nigeria. It is therefore imperative that the federal government prioritize research and establish functional Special Research Trust-Fund to oversee research funding in Nigeria.